The Effect of Interactive Engagement Strategy Using Quizizz on Students' Critical Thinking Ability on Chemical Bonding Material - Pratiwi, Yezsica; M.Noer, Asmadi; Anwar S, Lenny (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
The purpose of this research is to analyze the use of an interactive engagement strategy using Quizizz on students' critical thinking abilities on chemical bonding material. This research was carried out using a quasi-experimental design because not all factors that can influence learning can be controlled. This research was conducted in two experimental classes, namely the experimental class and the control class. The experimental class was given treatment in the form of an interactive engagement strategy using Quizlet, and the control class was given conventional model treatment. The sampling technique in this research is purposive sampling, which considers the homogeneity of the sample (class). The experimental and control class samples were 29 students from class X, MAN 1, Pekanbaru. The research results show that in particular, the ability to infer, namely making conclusions and presenting problems, dominates with the highest percentage value of 85%. On the other hand, analytical skills, which involve finding causes, assessing impacts, and predicting further impacts, recorded the lowest percentage, namely 50%. Overall, the average percentage for the four indicators reached 67.5%, which is in the good category. The results of the Independent Sample T-Test statistical test, with a significance value (sig) of 0.000, can be concluded that there is a significant difference in scientific literacy abilities between experimental class and control class students. From the N-Gain analysis, it is known that the average gain score for critical thinking skills in the experimental class (0.50 or 50%) is in the medium category, while the control class only reached 0.30 (30%), which is included in the low category. This conclusion shows that there is a more significant increase in learning outcomes for critical thinking skills in the experimental class compared to the control class